Minat Siswa Dalam Mengikuti Ekstrakurikuler Bola Voli di SMA Kecamatan Prabumulih Utara - kristina, putri cicilia; Mulyaniarti, Gusti; Ista, Ista; Darmawan, Riski; Anisa, Azola Dwi; Suwinto, Suwinto (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2023)
ABSTRACTThis research is to find out the studentd’ interest in joining volleyball extracurricular activities in SMA Prabumulih Utara Districk. This rearch uses qualitative research methods and data collection techniquest using an instrument in the form of a questionnaire, in this study illustrates how high the interest of students in joining volleyball extracurricular activities in SMA Prabumulih Utara District contained in SMA Negeri 1 Prabumulih and SMA PGRI Prabumulih. Overall data that has been studied related to students’ interest in volleyball extracurricular activities is strong. For the overall percentage in SMA Negeri 1 Prabumulih which IS 67,5% and for the overall percentage in SMA PGRI Prabumulih 66.5%. from the results of the analysis data it was concluded that the strongest interest in joining volleyball extracurricular activities was SMA Negeri 1 Prabumulih. Keywords: Interests;Volleyball Extracurricular;.